Preparation of the Biodegradable Lymphatic Targeting Imaging Agent Based on the Indocyanine Green Mesoporous Silicon System - Duan, Man; Han, Dongmei; Shen, Wenbin; Chang, Kun; Wang, Xinyu; Gao, Nan; Du, Jianshi (Frontiers in Chemistry, 2022)
The lymphatic system plays a crucial role in the immune system’s recognition and response to disease. Therefore, the imaging of lymphatic system, especially lymphatic vessels, has emerged as a valuable tool for diagnosis of metastasis. FDA-approved small-molecule dyes indocyanine green (ICG) have been widely applied to lymphatic vessels imaging. However, due to the small physical size, such molecules-based agents show no selectivity and rapid clearance from lymph nodes. Herein, a biodegradable lymphatic targeting imaging agent based on ICG-mesoporous silicon system (ICG@HMONs-HA) was obtained, which could not only target lymph-vessels, but also had a long residence time. The reported work provides a practical way for lymph-vessel fluorescence imaging and paves the way for clinical translation of nanomaterials-based tracers.